2022
DOI: 10.2147/jmdh.s362994
|View full text |Cite
|
Sign up to set email alerts
|

Sanfilippo Syndrome: Optimizing Care with a Multidisciplinary Approach

Abstract: Sanfilippo syndrome, or mucopolysaccharidosis type III (MPS III), is a disease grouping five genetic disorders, four of them occurring in humans and one known to date only in a mouse model. In every subtype of MPS III (designed A, B, C, D or E), a lack or drastically decreased activity of an enzyme involved in the degradation of heparan sulfate (HS) (a compound from the group of glycosaminoglycans (GAGs)) arises from a genetic defect. This leads to primary accumulation of HS, and secondary storage of other com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 96 publications
(166 reference statements)
0
5
0
Order By: Relevance
“…However, the results of other recent studies performed with a mouse model of MPS IIIA indicated that autistic-like behavior is caused by the increased proliferation of mesencephalic dopamine neurons not lysosomal dysfunction [72]. Notably, these outcomes are characteristic of children suffering from Sanfilippo disease [5,73,74]; hence, the mechanisms underlying to storage disorders are likely to be similar (or the same) in mice and humans. Detailed experiments with a mouse MPS IIIA model suggested that pathological modulation of dopamine activity can be a result of altered HS function, not elevated GAG levels [72].…”
Section: Discussionmentioning
confidence: 95%
“…However, the results of other recent studies performed with a mouse model of MPS IIIA indicated that autistic-like behavior is caused by the increased proliferation of mesencephalic dopamine neurons not lysosomal dysfunction [72]. Notably, these outcomes are characteristic of children suffering from Sanfilippo disease [5,73,74]; hence, the mechanisms underlying to storage disorders are likely to be similar (or the same) in mice and humans. Detailed experiments with a mouse MPS IIIA model suggested that pathological modulation of dopamine activity can be a result of altered HS function, not elevated GAG levels [72].…”
Section: Discussionmentioning
confidence: 95%
“…Such symptoms resemble those described in the preceding section ( Section 4 ) as characteristic of disorders associated with OXTR changes. Indeed, the symptoms of some MPS types, especially all subtypes of MPS III (Sanfilippo disease) are so similar to autism spectrum disorder or attention deficit hyperactivity disorder that MPS III is often misdiagnosed as one of these diseases [ 130 , 131 , 132 , 133 ].…”
Section: Oxtr In Mucopolysaccharidosesmentioning
confidence: 99%
“… Schematic representation of the various possibilities of applications of transcriptomic methods in studies on and practical use of CAR-T cells, reported to date in the literature, as depicted in the form of the Cyske rosette chart (a kind of the schematic summary as proposed by Cyske et al [ 85 ]). …”
Section: Figurementioning
confidence: 99%